(untitled) (Global Journal of Human-Social Science, 2016)
The challenge of sustainable development has provided nations a chance to correct the anomalies of development and provide a futuristic environment to attain positive goals Nigeria outsourcing for sustainable development became relevant and important in the light of the fact that she had signed the development protocols at the level of the United Nations and other international organizations Such include the Rio millennium development goals The Nigerian Diaspora provides an avenue to assist development Development theorists explain development as consequent upon the actions of government and civil society i e a partnership between government and civil society an arm of which is the Diasporai e International civil society Importantly the African foundation for development also noted that the quantum of remittance to the third world countries makes the Diaspora an important agent of change and development It is no wonder that the current trend is to tap into the resource base of the Diaspora This laudable project can only succeed where challenges that provide hindrances to the project are removed This paper examines the performance of the Diaspora Nigerians in development interventions It identifies the challenges facing the Diaspora Nigerians in their effort to respond to government outsourcing to encourage them to develop the